Genome-Wide Identification and Analysis of the AP2 Transcription Factor Gene Family in Wheat (Triticum aestivum L.) - Zhao, Yue; Ma, Renyi; Xu, Dongliang; Bi, Huihui; Xia, Zongliang; Peng, Huiru (Frontiers in Plant Science, 2019)
The AP2 transcription factors play important roles in regulating plant growth and development. However, limited data are available on the contributions of AP2 transcription factors in wheat (Triticum aestivum L.). In the present study, a total of 62 AP2 genes were identified in wheat from a genome-wide search against the latest wheat genome data. Phylogenetic and sequence alignment analyses divided the wheat AP2 genes into 3 clusters, euAP2, euANT, and basalANT. Chromosomal distribution, gene structure and duplication, and motif composition were subsequently investigated. The 62 TaAP2 genes were unevenly distributed on 21 chromosomes. Twenty-four homologous gene sets among A, B, and D sub-genomes were detected, which contributed to the expansion of the wheat AP2 gene family. The expression levels of TaAP2 genes were examined using the WheatExp database; most detected genes exhibited tissue-specific expression patterns. The transcript levels of 9 randomly selected TaAP2 genes were validated through qPCR analyses. Overexpression of TaAP2-10-5D, the most likely homolog of ArabidopsisANT gene, increased organ sizes in Arabidopsis. Our results extend our knowledge of the AP2 gene family in wheat, and contribute to further functional characterization of AP2s during wheat development with the ultimate goal of improving crop production.